Trajectory tracking controller for quadrotors using PID/MPC controller - Ho, Jia Wei (2019)
As technology progresses, it is evident that an increasing amount of processes are adopting the idea of 'autonomous'. One process that is being researched on is integrating an autonomous quadrotor to perform delivery task in replacement of manual delivery methods, which will improve delivery time.The main objective of this research is to design controllers that will achieve good performance in controlling a quadrotor to follow a preset trajectory for it. It is important that a quadrotor follow as closely as possible to a given trajectory to avoid any obstacles that will cause it to crash.At the beginning of this paper, di erent methods of deriving the quadrotor's mathematical model will be presented and discussed, namely Newton-Euler and Euler-Lagrange method. These mathematical models were derived considering all six degrees of freedom of a quadrotor in flight. In the next section of this paper, two di erent controllers were selected and mathematical model for each of them would be derived and explained. These controllers are namely, PID (Position-Integral-Derivative) controller and MPC (Model-Predictive-Control) controller. They were selected from a wide variety of controllers, because PID is simple to design and understand, and MPC has the ability to control the outputs simultaneously while considering possible interactions between system variables. MPC is also able to compute calculations with constraints imposed on both plant inputs and outputs. The last section of the paper will discuss and compare the performance of path tracking by these two controllers, as well as laying down the scope for future work on this research.